English Language Assessment: Pre-service Teachers’ Self-Reported Views (2023)
Both assessment and the teacher’s role as one of the main assessors of student learning are central components of the English teaching and learning process. This quantitative, non-experimental, and cross-sectional study seeks to explore preservice teachers’ perceived views, skills, and frequent practices towards English language assessment. The sample comprised 257 Chilean pre-service teachers, whose assessment perspectives were collected through three subscales. To analyze the data, mean scores and standard deviations were calculated. Additionally, a ttest was applied to identify statistical differences among participants’ responses, and an exploratory factor analysis was conducted to identify inter-related variables. Findings revealed participants’ views included that more training on assessment was necessary and that the purpose of assessment was monitoring the students’ learning progress. Regarding skills, participants expressed more confidence in formulating true or false items, assigning grades fairly, and providing written feedback. Furthermore, the participants’ most frequent assessment practices dealt with designing evaluations and providing feedback, rather than analyzing and communicating parametric results. The importance of this study lies in the understanding of how pre-service teachers perceived the assessment process and reflected upon their strengths, weaknesses, and assessment practices. Similar studies are encouraged to integrate the views, skills, and practices of in-service teachers of English. Keywords: language assessment literacy, language assessment, assessment skills, assessment practices, assessment self-perceived views